The Effect of Stop Stunting Video on Increasing Knowledge Pregnant Women about Stunting Prevention - Siti Muslimah; Sunartono .; Waryana . (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
The prevalence of stunting under five in Indonesia reaches 24.4% and Central Java Province reaches 20.8%, where Wonosobo Regency contributes 27.17%. One of the influencing factors is the mother's knowledge about stunting which is still low. The purpose of this research is to make a stop stunting video that can help increase mother's knowledge about stunting. This type of research is a quasi-experimental with a sample of 137 pregnant women. The results showed that there was a significant difference in maternal knowledge about stunting prevention in the posttest between the experimental group (education using video media) and the control group (education using leaflet media) because the significance value of the independent sample t test was 0.000 or less than 0.05. . The score gain in the experimental group is 77.14%, the value is included in the effective category or has a high level of effectiveness, while in the control group, 23.37% the value is included in the ineffective category. So that the stop stunting video media has a high level of effectiveness to increase mother's knowledge about stunting prevention compared to leaflet media. As for the effect size of the video media, the d value is 1.42, which means it has a large effect.